INTERPRETASI NILAI-NILAI EDUKATIF LAGU KAMBANGLAH BUNGO UNTUK MEMBANGUN KARAKTER PESERTA DIDIK (Suatu Analisis Hermeneutik) - Desyandri Desyandri (Fakultas Bahasa dan Seni UNP, 2016)
This article aims to interpret the educational values which embodied in the song of Kambanglah Bungo created by Syofyan Naan. The process of interpretation is done by a multidisciplinary hermeneutic analysis. Interpretation is generated by associating the aspects of language, music/songs, psychological, socio-cultural, and education, so that has five (5) educational values, namely: (1) love the realm of Minang, (2) awareness and self-esteem, (3) concern and responsibility, (4) alert and surveillance, (5) discipline. Educational values serve as the vehicle for educating the students to create the actions and behaviors that reflect the character of the Minang people. Education and learning as a means of inheritance of cultural values is obliged to explore, actualize, socialize, and civilize these values in a sustainable way in order to build the character of students that habitual and cultured.